Studying the role of protein deamidation in neurodegenerative disease in proteome-wide scale - Ang, Yi Lin (2014)
Deamidation had been associated with amyloid-β peptide and tau protein aggregation in Alzheimer’s disease. Our previous study detected dysregulation of membrane proteins in vascular dementia, and a review of the data revealed extensive deamidation of Na+/K+- ATPase. Taken together, deamidation might be a significant modification to membrane and insoluble proteins in neurodegenerative diseases. However, nonenzymatic deamidation can occurs either in vivo or during sample preparation and its discrimination remains challenging. Therefore, to elucidate the association and impact of deamidated proteins in neurodegeneration, and to minimize nonenzymatic deamidation during sample preparation, this work focused on developing protocol for enriching membrane and insoluble proteins. The protocol adopting differential high-speed centrifugation and ultracentrifugation were tested on a human brain tissue, and differential centrifugation was found to be suitable for enriching membrane and insoluble proteome in brain tissues. Approximately 50% (679 proteins) of the total identified proteins using differential high-speed centrifugation were membrane proteins and 66.7% (290 proteins) more integral proteins were identified compared to ultracentrifugation (174 proteins). In the future, protein deamidation can be studied by enriching membrane and insoluble proteins with differential centrifugation to establish the link between deamidation and neurodegenerative diseases.